Sleepless in Seattle No Longer - Reich, Joshua; Goraczko, Michel; Kansal, Aman; Padhye, Jitu (2010)
In enterprise networks, idle desktop machines rarely sleep, because users (and IT departments) want them to be always accessible. While a number of solutions have been proposed, few have been evaluated via real deployments. We have built and deployed a sleep proxy system at Microsoft Research. Our system has been operational for six months, and has over 50 active users. To the best of our knowledge, this paper is the first to report on lessons learned from building, deploying and running a sleep proxy system on a real network. Overall, we find that our system allowed user machines to sleep quite well (most sleeping over 50% of the time), but much potential sleep time was missed due to IT management tasks that play havoc with machine sleep. We suggest a number of ways to fix this problem. We also discover and address a number of issues overlooked by prior work, including complications caused by IPsec. We found certain popular cloud-based applications did not work well with our design, and we deployed an ad-hoc fix to the problem. We believe our experience and insights will proveuseful in guiding the design of future sleep solutions for enterprise networks.